(untitled) (The Review of Diabetic Studies, 2025)
This article reviews the critical role of paramedics in pre-hospital emergency care, focusing on their interventions, decision-making, and impact on patient survival and recovery. By analyzing global evidence, the paper highlights how paramedics bridge the gap between the site of injury/illness and definitive hospital care. Key areas include trauma management, cardiac arrest response, airway management, and integration of advanced technologies such as telemedicine. The review also addresses challenges like resource limitations, training variability, and inter-professional collaboration. The findings emphasize the need for standardized protocols, continuous professional development, and innovative models to enhance the effectiveness of pre-hospital emergency services.